Three Candidate Probiotic Strains Impact Gut Microbiota and Induce Anergy in Mice with Cow's Milk Allergy - Esber, Nathalie (Appl Environ Microbiol, 2020)
Cow’s milk allergy is a worldwide public health issue, especially since there is no effective treatment, apart from milk and dairy product avoidance. The aim of this study was to assess the beneficial role of three probiotic strains previously selected for their prophylactic properties in a mouse model of β-lactoglobulin allergy. Administration of Lactobacillus rhamnosus LA305, L. salivarius LA307, or Bifidobacterium longum subsp. infantis LA308 for 3 weeks post–sensitization and challenge modified the composition of the gut microbiota, with an increase in the Prevotella NK3B31 group and a decrease in Marvinbryantia, belonging to the Lachnospiraceae family. Although no impact on markers of sensitization was detected, modifications of foxp3, tgfβ, and il10 ileal gene expression, as well as plasma metabolomic alterations in the tryptophan pathway, were observed. Moreover, ex vivo studies showed that all probiotic strains induced significant decreases in cytokine production by β-lactoglobulin-stimulated splenocytes. Taken together, these results suggest that the three probiotic strains tested lead to alterations in immune responses, i.e., induction of a tolerogenic anergy and anti-inflammatory responses. This anergy could be linked to cecal microbiota modifications, although no impact on fecal short-chain fatty acid (SCFA) concentrations was detected. Anergy could also be linked to a direct impact of probiotic strains on dendritic cells, since costimulatory molecule expression was decreased following coincubation of these strains with bone marrow-derived dendritic cells (BMDCs). To conclude, all three candidate probiotic strains induced strain-specific gut microbiota and metabolic changes, which could potentially be beneficial for general health, as well as anergy, which could contribute to oral tolerance acquisition. IMPORTANCE We showed previously that three probiotic strains, i.e., Lactobacillus rhamnosus LA305, L. salivarius LA307, and Bifidobacterium longum subsp. infantis LA308, exerted different preventive effects in a mouse model of cow’s milk allergy. In this study, we evaluated their potential benefits in a curative mouse model of cow’s milk allergy. When administered for 3 weeks after the sensitization process and a first allergic reaction, none of the strains modified the levels of sensitization and allergic markers. However, all three strains affected gut bacterium communities and modified immune and inflammatory responses, leading to a tolerogenic profile. Interestingly, all three strains exerted a direct effect on dendritic cells, which are known to play a major role in food sensitization through their potentially tolerogenic properties and anergic responses. Taken together, these data indicate a potentially beneficial role of the probiotic strains tested in this model of cow’s milk allergy with regard to tolerance acquisition.